The enlightenment Qur'an: the politics of translation and the construction of Islam - Elmarsafy, Ziad (A Oneworld book, 2009)
Iconoclastic and fiercely rational, the European Enlightenment witnessed the birth of modern Western society and thought. Reason was sacrosanct and for the first time, religious belief and institutions were open to widespread criticism. In this groundbreaking book, Ziad Elmarsafy challenges this accepted wisdom to argue that religion was still hugely influential in the era. But the religion in question wasn`t Christianity - it was Islam. Charting the history of Qur`anic translations in Europe during the 18th and early 19th Centuries, Elmarsafy shows that a number of key enlightenment figures - including Voltaire, Rousseau, Goethe, and Napoleon - drew both inspiration and ideas from the Qur`an. Controversially placing Islam at the heart of the European Enlightenment, this lucid and well argued work is a valuable window into the interaction of East and West during this pivotal epoch in human history.